PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUALTERHADAP KINERJA KARYAWAN - Winda Desta Riani; Ni Nyoman Suryani; Gde Bayu Surya Parwita (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
Organizational objectives can be achieved maximally if supported by good performance from employees within the organization. To get good performance from employees, a structured and effective direction must be sought to move its employees to want to work more productively in accordance with the organization's stated goals, many factors that influence the performance of employees including intellectual intelligence, emotional intelligence, and spiritual intelligence. This research was conducted with the aim of "To determine the effect of intellectual intelligence, emotional intelligence, and spiritual intelligence both partially and simultaneously on employee performance". The method of determining the sample in this study uses Saturated Sampling method. While the analysis technique used is multiple linear regression statistical analysis techniques. Based on the results of the analysis and discussion, it can be concluded that: (1) Intellectual intelligence has a positive and partially significant effect on employee performance. (2) Emotional intelligence has a positive and significant effect partially on employee performance. (3) Spiritual intelligence has a positive and partially significant effect on employee performance. (4) Intellectual intelligence, emotional intelligence and spiritual intelligence simultaneously have a positive and significant effect on employee performance.